A SWOT analysis of the complex interdependencies of the Maltese reimbursement processes - Katharina Abraham; Margreet Franken (Elsevier, 2023)
Background: The processes that operationalize the evaluation framework for new medicines are implemented to reach the system objectives of public health, financial sustainability, and equitability. However, when the activities and procedures of these processes are misaligned, the objectives of the system may be at risk. Objectives: To evaluate the supporting processes for introducing new medicines in public healthcare services in Malta. Methods: We first reviewed literature on the Maltese reimbursement system and subsequently conducted semi-structured interviews based on the Hutton Framework. Interviewees included policy makers, committee members, procurement staff, medical specialists, pharmacists, and pharmaceutical industry representatives. After validation, we analysed the data with a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Results: Most medicines are assessed for introduction on the Government Formulary List. Exceptional requests fall outside this policy and pass through the Exceptional Medicinal Treatment route. Efficiency, quality, and transparency are major weaknesses across the supporting processes. Taking up responsibility, however, is considered the most important factor in reaching system objectives. Stakeholders tend to shift responsibilities to other processes, start/stop activities that impact the activities of subsequent processes whilst dismissing any contribution to the weaknesses of the system. Consequently, system objectives cannot be reached in an optimum manner. Conclusions: The Maltese case showed that recommendations for introducing new medicines in the public healthcare setting are influenced beyond the choice of HTA tools and criteria. Earmarked budgets, political steering, delays, and uninformed applicants as well as HTA capacity are impeding on system goals of public health, equity, and sustainability.